Evaluacion de mezclas forrajeras de invierno en las regiones norte de la provincia de Misiones, Argentina, y sudoeste de Paraná, Brasil - Arenhardt, Matias Esteban (2024)
During the winter months in Northeast Argentina and Southern Brazil, there is a marked decrease in forage production due to low temperatures and reduced availability of sunlight, which affects both the digestibility and nutrient content of the forage. The use of annual winter forages is presented as an alternative for production in crop-livestock systems, with the aim of overcoming the forage deficit. This study aimed to evaluate the dynamics of winter forage and mixture production by determining dry matter and the nutritional value of different cultivars, to identify which ones are best adapted to these regions. The experiment was carried out in the productive unit of the Faculty of Forestry Sciences, Misiones, Eldorado and in the experimental area of the Federal Technological University of Paraná, Pato Branco campus. The cultivars evaluated were: milton oats, maximus ryegrass, BRS integração ryegrass, estações ryegrass, BRS piquete vesicular clover, BRS pasture wheat, border oats, IPR emerald oats, BRS posteiro lotus lotus, red mixer clover, interleaf white clover and BRS 139 black oats. The experimental design was randomized blocks, divided into 10 treatments of mixtures and cultivars with 4 repetitions. Sowing was carried out in May 2022. Nitrogen fertilization was carried out with urea at a rate of 150 kg/ha of Nitrogen in two stages. Total production (PTF) and per cutting, daily accumulation rate, plant density (NPL) and nutritional values were calculated. In Eldorado, the treatments RGI+RGM+TP (Ryegrass BRS Integration, Ryegrass Maximus and Vesicular Clover BRS Piquete) (5.9 Tn/ha) and RGM (Ryegrass Maximus) (5.8 Tn/ha) stood out for their high forage production. In Pato Branco, RGE (Ryegrass Estações) (11.3 Tn/ha) and MIX (Avena Fronteira, Avena negra) (10.9 Tn/ha) were the most productive. In terms of nutritional value, AVM (Avena Milton) presented the highest crude protein content in both periods.